Multiscale simulation on thermal stability of supported metal nanocatalysts. (25th January 2019) - Deng, Shengwei; Qiu, Chenglong; Yao, Zihao; Sun, Xiang; Wei, Zhongzhe; Zhuang, Guilin; Zhong, Xing; Wang, Jian‐guo
Abstract : Supported metal nanocatalysts offer a wide range of promising applications because of their many enhanced catalytic properties arising from highly active species dispersed onto a high surface area support. Developing a deep understanding of thermal stability is of great importance to avoid irreversible catalyst deactivation. It is generally acknowledged that many factors including the chemical composition, morphology, support material, metal–support interaction, reaction condition and environment have significant impacts on the thermal stability. The rapid developments of computational capacity and advanced simulation techniques allow one to correlate the structure–property relationships at the atomic level. In this review, the widely used simulation methods and computational strategies on supported metal nanocatalysts will be briefly introduced. Next, we will summarize the theoretical models of structure evolution of nanoparticles and describe the calculation of metal–support interaction, accompanying with intra‐ and inter‐particle sintering process in the vacuum or reaction environments, and then give perspectives on the future directions towards better utilization of various simulation techniques. This article is categorized under: Structure and Mechanism > Reaction Mechanisms and Catalysis Structure and Mechanism > Computational Materials Science Abstract : The rapid developments of computational capacity and advanced simulation techniques allow one to develop a deep understanding of thermal stability of supported metal nanocatalysts, which is important to avoid irreversible catalyst deactivation.